Low and high linear energy transfer radiation sensitization of HCC cells by metformin - KIM, Eun Ho (Oxford University Press, 2014)
The purpose of this study was to investigate the efficacy of metformin as a radiosensitizer for use in combination therapy for human hepatocellular carcinoma (HCC). Three human HCC cell lines (Huh7, HepG2, Hep3B) and a normal human hepatocyte cell line were treated with metformin alone or with radiation followed by metformin. In vitro tests were evaluated by clonogenic survival assay, FACS analysis, western blotting, immunofluorescence and comet assay. Metformin significantly enhanced radiation efficacy under high and low Linear Energy Transfer (LET) radiation conditions in vitro. In combination with radiation, metformin abrogated G2/M arrest and increased the cell population in the sub-G1 phase and the ROS level, ultimately increasing HCC cellular apoptosis. Metformin inhibits the repair of DNA damage caused by radiation. The radiosensitizing effects of metformin are much higher in neutron (high LET)-irradiated cell lines than in γ (low LET)-irradiated cell lines. Metformin only had a moderate effect in normal hepatocytes. Metformin enhances the radiosensitivity of HCC, suggesting it may have clinical utility in combination cancer treatment with high-LET radiation.